ANALISIS KAPASITAS PETANI KAKAO DESA PONGGI KECAMATAN POREHU KABUPATEN KOLAKA UTARA - ASHAR; M. Zainal S; Andi Rizkiyah Hasbi (Innofarm : Jurnal Inovasi Petanian, 2025)
This study aims to determine the capacity analysis of cocoa farmers in Ponggi Village, Porehu District, North Kolaka Regency, Southeast Sulawesi Province. This research method is a quantitative descriptive method, with data collected through observation, interviews, documentation, and the distribution of questionnaires to cocoa farmers. The results of the study indicate that information support— support from fellow farmers, internet support, and support from buyers/collectors—significantly influences cocoa farmers' capacity. At the same time, the extension activity variables—methods, materials, and communication frequency—did not substantially affect cocoa farmers' capacity. Meanwhile, the reflected farmer characteristics variables (methods, materials, and frequency of communication) do not significantly affect cocoa farmers' capacity. Keywords: Capacity; Cocoa Farmers, Extension Activities; Information Support